Improving Social Studies Learning Achievement Through the Application of E-Comic Learning Media - Evi Ariyanti Marlina Sihombing; Kartika Sari; Rachyana Fahira; Rosvilani Saragih; Rosidah Minta Ito Pasaribu; Sugiharto Sugiharto; Syarifah Syarifah (STAI Miftahul Ula Nganjuk, 2024)
This study aims to enhance student achievement in social studies through the application of e-comic learning media. Data were collected using a learning achievement test, and both qualitative and quantitative data were analyzed descriptively. The findings indicate that the use of e-comic learning media effectively improves student learning achievement. Initial results showed an average score of 60.76, which increased to 70.51 in the first cycle and 79.74 in the second cycle. Additionally, the percentage of student learning completion improved significantly, from 30.76% at the outset to 82.05% in the first cycle, and ultimately reaching 100% in the second cycle. The study concludes that implementing e-comic learning media can significantly enhance student achievement in social studies.